2017
DOI: 10.1111/ijal.12167
|View full text |Cite
|
Sign up to set email alerts
|

Reflexivity and academic writing: How supervisors deal with self‐discovery in student teachers' bachelor's theses

Abstract: In light of the Bologna reform, professional and vocational schools have progressively moved towards becoming formal higher education institutions. In this context, Universities of Teacher Education (UTE) in Switzerland have undergone significant changes with respect to their role in society over the past decades. One of the major changes in this process concerns the training of research skills in formal teacher education. Part of this training includes writing assignments, such as the bachelor's thesis, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In accordance with the strategy of teaching, Solin (2018) has highlighted the importance of teaching portfolio in academic recruitment. In line with it, Studer (2017) emphasizes the need for conducting reflexivity in academic writing.…”
Section: Introductionmentioning
confidence: 96%
“…In accordance with the strategy of teaching, Solin (2018) has highlighted the importance of teaching portfolio in academic recruitment. In line with it, Studer (2017) emphasizes the need for conducting reflexivity in academic writing.…”
Section: Introductionmentioning
confidence: 96%
“…7 However, the academic setting that is to support nursing students in conducting their independent degree project and writing scientific texts is highly variable and sometimes inadequate. Previous studies have shown that nursing students feel their first years of education do not prepare them for developing scientific academic texts or for reflective writing with a sufficient level of academic rigor, 8 but mainly for a synthetic type of writing required in clinical scenarios. 9 Several models have been proposed for supporting students and providing them with the skills needed to write their degree projects.…”
Section: Introductionmentioning
confidence: 99%
“…The different writing assignments that students must complete during the course of their degrees (e.g. final theses, seminar papers, practice reports, reflective diaries) are crucial in implementing research‐based learning (Studer, ). Academic writing is understood as the activity of constructing an original text using external texts (intertextuality) that gives rise to a final product which is the result of different written explanations and arguments (Teberosky, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both reflexive and academic writing should involve a uniform and systematic process throughout the different degree courses. However, there is a wide gap between personal‐reflective writing tasks and those that focus on the development of scientific writing skills (Studer, ). Most writing tasks in university courses focus on reflective writing activities, which are highly useful for the development of critical thinking but, in many instances, lack academic rigor (Studer, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation